Dietary Phenolic Compounds Interfere with the Fate of Hydrogen Peroxide in Human Adipose Tissue but Do Not Directly Inhibit Primary Amine Oxidase Activity. (5th January 2016) - Carpéné, Christian; Hasnaoui, Mounia; Balogh, Balázs; Matyus, Peter; Fernández-Quintela, Alfredo; Rodríguez, Víctor; Mercader, Josep; Portillo, Maria P.
Abstract : Resveratrol has been reported to inhibit monoamine oxidases (MAO). Many substrates or inhibitors of neuronal MAO interact also with other amine oxidases (AO) in peripheral organs, such as semicarbazide-sensitive AO (SSAO), known as primary amine oxidase, absent in neurones, but abundant in adipocytes. We asked whether phenolic compounds (resveratrol, pterostilbene, quercetin, and caffeic acid) behave as MAO and SSAO inhibitors. AO activity was determined in human adipose tissue. Computational docking and glucose uptake assays were performed in 3D models of human AO proteins and in adipocytes, respectively. Phenolic compounds fully inhibited the fluorescent detection of H2 O2 generated during MAO and SSAO activation by tyramine and benzylamine. They also quenched H2 O2 -induced fluorescence in absence of biological material and were unable to abolish the oxidation of radiolabelled tyramine and benzylamine. Thus, phenolic compounds hampered H2 O2 detection but did not block AO activity. Only resveratrol and quercetin partially impaired MAO-dependent [ 14 C]-tyramine oxidation and behaved as MAO inhibitors. Phenolic compounds counteracted the H2 O2 -dependent benzylamine-stimulated glucose transport. This indicates that various phenolic compounds block downstream effects of H2 O2 produced by biogenic or exogenous amine oxidation without directly inhibiting AO. Phenolic compounds remain of interest regarding their capacity to limit oxidative stress rather than inhibiting AO.